Identification of the Potentialities of Ecotourism - Mohammad Hadi Khorsand; Mohammad Taghipour (International Journal of Climate Conditions, 2024)
Khalkhal town's climate, geography, topography, ecological conditions, vegetation, and green spaces make it an exceptional tourism destination. Located in the Talesh foothills, Khalkhal enjoys a favorable climate and abundant water resources, attracting nature lovers. To unlock the town's tourism potential, it is crucial to assess its diverse attributes. Information layers such as slope, geographical direction, vegetation, and climate are individually analyzed. The best zones for the development of ecotourism in Khalkhal are then determined by superimposing these layers in a GIS and applying the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The study prioritizes zones for various tourism activities, including ecotourism, skiing, nature tourism, foothill, and mountain climbing. Findings reveal that the region has substantial potential for both ecotourism and geotourism attractions. Realizing this potential requires strategic planning and development, focusing on sustainable tourism practices that preserve the natural environment while highlighting Khalkhal's unique attractions. When managed and promoted well, Khalkhal might become known as a top travel destination for travelers looking for outdoor activities and scenic views. Additionally, the construction of essential infrastructure—like paths, lodging, and educational signage—will improve the visitor experience even more and guarantee that Khalkhal lives up to the expectations of a wide range of travelers. Over time, this all-encompassing strategy will not only support the town's tourism business but also help it flourish, establishing Khalkhal as a top destination for outdoor recreation and stunning scenery.
Keywords: Ecotourism; Natural Environment; TOPSIS; geotourism; sustainable development